KAJIAN SUMBER DAYA MANUSIA DALAM PROSES REKRUTMEN TENAGA KERJA DI PERUSAHAAN - Setiani, Baiq (Jurnal Ilmiah Widya, 2013)
Employee is the asset of a company. The productivity is based on the employeesâ€™ performance which is in accordance with the principles of â€œthe right man in the right placeâ€ in order to achieve the companyâ€™s goal. The first step in placing the right person is by doing the recruitment and selection of the human resources who are suitable and have a high motivation in doing the jobs. The objective of this study is to find out the process, the purpose and the difficulties in the recruitment process. and the obstacles. The method used is literature research with descriptive and explorative approach. It can be concluded that : (1) The well arranged recruitment and selection strategy will deliver positive results for the company, (2) To have the companyâ€™s highest performance should be supported by the good quality of the employees, (3) The more effective the recruitment, the better the employee will be, (4) There are some obstacles in the recruitment process such as the companyâ€™s regulation, habit of the possible employees and external factors of the companyâ€™s surrounding.